Analisis Perbandingan Kinerja Keuangan Pt Unilever Indonesia Tbk, Pt Telkom Indonesia Tbk, Dan Pt Bank Mandiri Dalam Kondisi Inflasi Dan Suku Bunga - Bayu Surya Ramadhan; Eva Dwi Fani; Istiono Istiono (CV. SINAR HOWUHOWU, 2026)
This literature review performs a comparative analysis of financial performance among three major Indonesian blue-chip companies, namely PT Unilever Indonesia Tbk from the consumer goods sector, PT Telkom Indonesia Tbk from the telecommunications sector, and PT Bank Mandiri (Persero) Tbk from the banking sector, under the influence of inflation and Bank Indonesia interest rate policies during the period 2022–2025. The study aims to compare key financial ratios across sectors and identify sectoral sensitivities as well as mitigation strategies employed by each company. Using a qualitative descriptive comparative literature review approach, data were synthesized from 20 peer-reviewed journal articles and theses published between 2019 and 2025 through purposive sampling and thematic synthesis. The findings indicate clear sectoral differences: PT Unilever Indonesia Tbk faces significant pressure on profitability and liquidity due to rising raw material costs caused by inflation, PT Bank Mandiri (Persero) Tbk exhibits high sensitivity to interest rate changes affecting net interest margin, while PT Telkom Indonesia Tbk shows moderate resilience with stable asset turnover. Consumer goods companies are more vulnerable to inflation, banking institutions are heavily impacted by BI Rate fluctuations, and telecommunications firms maintain relatively balanced performance. This review highlights the importance of sector-specific financial strategies and provides practical implications for corporate management and investors in navigating macroeconomic volatility to ensure long-term sustainability in Indonesia’s competitive economy.